Enhanced MRI and MRI-Guided Interventional Procedures in Women with Asymptomatic Silicone-Injected Breasts - Yun-Chung Cheung; Shin-Chih Chen; Yung-Feng Lo (The Scientific World Journal)
Asymptomatic women who have received silicone injection for breast augmentation have a risk of underestimating breast cancer by palpation, mammography, or breast sonography. Enhanced breast MRI is sensitive to display certain nonspecific enhanced lesions or suspicious lesions. Such nonspecific MRI-detected lesions could be managed by American College Radiology BI-RADS lexicon and selectively with MRI-guided techniques biopsy to prevent unnecessary surgery.